The Kiss of Death: Serratia marcescens Antibacterial Activities against Staphylococcus aureus Requires Both de novo Prodigiosin Synthesis and Direct Contact - Sungbin Lim; Jihun Bhak; Sungwon Jeon; Wonsik Mun; Jong Bhak; Seong Yeol Choi; Robert J. Mitchell (Microbiology Spectrum, 2022)
ABSTRACT Prodigiosin possesses antibacterial activities, but as a highly hydrophobic compound, it raised the question about how Serratia marcescens introduce this compound to other microbes. Here, we demonstrate that the production of prodigiosin by newly isolated S. marcescens RH10 correlates with its antibacterial activity against a multidrug-resistant strain of S. aureus, with this pathogen’s viability decreasing 6-log over 24 h. While S. marcescens RH10 does secrete membrane vesicles that carry prodigiosin, this antibiotic was not active in this form, with 5 mg/L prodigiosin leading to only a 1.22-fold reduction in the S. aureus viability while the same quantity of purified prodigiosin led to a 2800-fold reduction. Contact assays, however, showed increased activity, with a 3-log loss in the S. aureus viabilities in only 6 h as long as de novo production of prodigiosin occurred. The role of prodigiosin was confirmed further by generating an isogenic ΔpigA mutant in S. marcescens RH10, based on the draft genome sequence reported here, to inhibit the synthesis of prodigiosin. In all experiments performed, this mutant was unable to kill S. aureus. Finally, the possibility that the type VI secretion system present in S. marcescens may also be important was also explored as it is known to be used by this strain to kill other microbes. The results here, however, found no obvious activity against S. aureus. In conclusion, the results presented here show prodigiosin requires both cell-to-cell contact and de novo synthesis for it to be effective as an antibiotic for its native host. IMPORTANCE The antibacterial activities of prodigiosin are well-established but, as a hydrophobic molecule, the mechanisms used to introduce it to susceptible microbes has never been studied. We found here, in contrast to violacein, another hydrophobic antibiotic that can be transferred using membrane vesicles (MVs), prodigiosin is also carried from Serratia marcescens in MVs released but its resulting activities were severely mitigated compared to the freely added compound, suggesting it is more tightly bound to the MVs than violacein. This led us to hypothesize that cell-to-cell contact is needed, which we demonstrate here. As well, we show de novo synthesis of prodigiosin is needed for it to be effective. As violacein- and prodigiosin-producing bacterial strains are both beneficial to amphibians, where they help protect the skin against pathogens, the findings presented here provide an important ecological perspective as they show the mechanisms used differ according to the antibacterial produced.